The economic analyses of the UK prospective diabetes study. - Gray, A; Clarke, P (2008)
An economic analysis was not initially included in the study design of the UK Prospective Diabetes Study (UKPDS). However, data were collected throughout the study on hospital drugs and medications used and these were supplemented near the end of the study by cross-sectional surveys of non-inpatient healthcare use and quality of life. Evaluations of tight vs. less tight blood pressure control, intensive vs. less conventional blood glucose control and metformin showed that each was highly cost-effective and that all could be provided at modest total cost. Further analyses showed that amputations and stroke had particularly severe consequences for quality of life, and that amputations and non-fatal MI had high cost consequences. Finally, patient-level data were used to construct a diabetes outcomes model, which estimates the probability of longer-term complications from patient-specific risk factors and can be used in populations at different stages of diabetes progression. The economic analyses arising from the UKPDS have provided new evidence to clinicians, policymakers and researchers on the consequences of diabetes and the cost-effectiveness of interventions, thereby assisting the development of treatment guidelines and improved standards of care. The analyses also illustrated a number of methodological innovations. Finally, the UKPDS Outcomes Model is gaining widespread acceptance as a validated tool for long-term economic and clinical prediction in diabetes.